Influence of nozzle diameter and gas flow on spatter removal in laser powder bed fusion: A CFD approach - Awad B.S. Alquaity (Results in Engineering)
In laser powder bed fusion (LPBF), effective spatter removal is vital for maintaining consistent build quality and mechanical properties of the printed part. This study explores the impact of geometric modifications to the LPBF build chamber on spatter removal for stainless steel 316L powder, focusing on three inlet nozzle diameters of 6, 12, and 18 mm. Using turbulent inert gas flow and the discrete phase model (DPM) in CFD simulations, spatter particles were individually tracked to predict their trajectories in the LPBF build chamber. Spatter trajectories were analyzed at ejection velocities of 1.5 m/s and 4.5 m/s, and angles of 45° and 70°, for spatter diameters of 60, 110, and 160 µm from nine ejection locations. The results indicate that inert gas velocity significantly influences spatter trajectories, with reverse flow leading to redeposition at certain locations on the build plate. The 6 mm nozzle achieved the highest spatter removal, with 35.2% at 1.5 m/s and 81.5% at 4.5 m/s. Spatter removal efficiency varied by ejection location, being lowest near the inlet for all nozzle sizes. Therefore, printing parts beyond the quarter point of the build plate is recommended. Additionally, smaller spatter ejected at lower angles generally achieved higher removal, suggesting that using smaller metal powder may further enhance spatter removal.